Hubungan Durasi Menderita Diabetes Melitus Tipe 2 dengan Kejadian Katarak di RSUD DR. H. Abdul Moeloek Provinsi Lampung Tahun 2018 - Nadyanti, Febri; Himayani, Rani; Putri, Giska Tri; Yusran, M (Essential: Essence of Scientific Medical Journal; Vol 17 No 1 (2019): Volume 17 No. 1 (Januari-Juni 2019) ESSENTIAL: Essence Of Scientific Medical Journal, 2019)
Background: Cataract is one of the complications in type 2 diabetes mellitus caused by the buildup of sorbitol. The factors that influence occurrence of cataract is the duration of suffering type 2 diabetes mellitus. Purpose: The aim of this study was to determine the relationship among duration of type 2 diabetes mellitus with the occurrence of cataract in general hospital RSUD DR. H. Abdul Moeloek Lampung Province in 2018. Method: The design used in this study was observational analytic with a cross-sectional approach. There were 30 samples of patient with type 2 diabetes mellitus in the general hospital RSUD DR. H. Abdul Moeloek Lampung Province in 2018. Samples were chosen by total sampling and the data was analyzed by using chi square. Result: Duration of suffering from type 2 diabetes mellitus >10 years was as much as 40%, while 60% duration was ?10 years. From 30 participants, 53,3% had cataract and 46,7% had no cataract. Duration of suffering type 2 diabetes mellitus was statistically related with the occurrence of cataract with p value = 0,000 (p<0,05). Conclusion: Based on this study, we can conclude that there was a relation between duration of type 2 diabetes mellitus with the occurrence of cataracts in general hospital RSUD DR. H. Abdul Moeloek Lampung Province in 2018.   Keywords: Cataract, Duration of Type 2 Diabetes Mellitus, Sorbitol